Modelo heurístico híbrido para el ruteo vehicular y manejo de inventario en una entidad comercializadora de combustibles - Jorge Israel Frometa Moya; Javier de Jesús Pérez Campos (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– The inventory routing problem is a complex topic recognized by the scientific literature. This work shows up this kind of problem, particularly a problem with freight traffic indicator as an objective for optimization, also a mathematical model and procedure for the resolution of this problem in an entity that sales fuel in eastern region of Cuba. For it, we were used heuristics combined methods of decomposition and reduction, integrated with binary linear programming, for the determination of the routing for vehicles toward the clients. The objective was to simplify the problem and to offer a satisfying performance based on the achievement of inventory levels according to a planned covering level, the rational use of the vehicles. Finally, it was proven in a case of study based on a real operative situation of the company studied.
Keywords: C61; 330; vehicle routing problem; inventory management; heuristics methods; binary linear programming